Organization of exhibition spaces based on botanical gardens - Rozhak-Lytvynenko, Kseniia; Нorupakha Vita (Theory and practice of design, 2021)
oday, open exhibition spaces are of special interest as one of the types of urban general recreational spaces and objects of landscape architecture that have scientific, technical, social, economic and cultural significance. Open-air exhibitions have been used since ancient times, and even then they were considered an effective source of information. They were organized most often for the purpose of public demonstration of results of any creative process, kinds of art, achievements in various spheres, display and popularization of historically valuable objects of biological species of representatives of flora and fauna, etc. — in the form of an artificially created object-spatial environment under the open sky. Currently, exhibition activity is considered as a form of advertising communications. Analyzing the development of exhibition spaces and complexes, it can be noted that the authors’ creative ideas have always been based on the search for original architectural, planning and artistic solutions, which reflected, inter alia, the development of science and technology. In addition, the theme of the exhibition is an important factor in the organization of the subject-spatial environment. The exposition activity of botanical gardens in Ukraine, as well as in other countries, is of great importance and is gaining exceptional popularity. Obviously, with the right feed, the plant kingdom is able to impress the imagination of most people, and the experience of the world’s leading botanical gardens at the moment has already proved this. Over time, comes the realization that the role of botanical gardens in society must grow steadily, and the range of activities - to expand, and this is due primarily to the growing needs of society, but also, in many respects, with the economic model of botanical gardens, public funding of which in our time has virtually ceased. That is why botanical gardens in Ukraine need to resume the practice of holding various botanical, horticultural, plant, landscape-architectural and other exhibitions and festivals.